Factors affecting the intention to adopt farm animal welfare disclosures in sustainability reporting: evidence from listed food companies in Sri Lanka - Samaraweera, Saviesha; Manawadu, Isuru (Frontiers in Animal Science, 2024)
Animal welfare is a critical concern for the food industry, and companies must take responsibility for managing their policies and procedures to ensure the welfare of farm animals. However, many companies fail to prioritize animal welfare in their reporting. This study applies the theory of planned behavior to examine how behavioral factors—such as attitude, subjective norms, perceived behavioral control, and awareness of farm animal welfare—influence the intentions of individuals involved in sustainability reporting to include farm animal welfare disclosures in the sustainability reports of listed food companies in Sri Lanka. This study focuses on individuals involved in the sustainability reporting process of publicly listed food companies in the Colombo Stock Exchange. Out of 124 companies which were engaged in the food sector as derived from GICS industry classification index, the study identified 61 companies by isolating companies having a farm animal footprint along its’ supply chain which involved an individual analysis of the products offered by the company. The survey approach was used for this study with 110 self-administered questionnaires being distributed among individuals in the designations of CFOs, Directors, Managers, Accountants, assistant managers, Accounts assistants/executives and associates. Data were analyzed using structural equation modeling (PLS-SEM). The findings reveal that only perceived behavioral control and subjective norms have a significant positive impact on the intention to adopt farm animal welfare disclosure practices among those engaged in the sustainability reporting process of listed food companies. This study is important because it highlights the need for standardized guidelines and mandatory regulations for animal welfare reporting in Sri Lanka, offering insights for policymakers and institutions to improve sustainability practices and establish stringent farm animal welfare reporting standards.